The effect of personality traits (Big-Five), materialism and stress on Malaysian generation Y compulsive buying behaviour - Mat Rahim, Fatin Farwizah; Abdul Rahim @ Abdul Wahab, Husniyah (Human Resource Management Academic Research Society, 2018)
The continuous activities of productions and consumptions can help the economic growth of a country. However, excessive spending by consumers who want to keep up with various productions of goods and services can eventually be harmful as for their financial and psychological well-being. This study aims to determine the effect of personality traits (Big-Five), materialism and stress on Malaysian generation Y compulsive buying behaviour. Self-administered questionnaires were distributed to the respondents which were drawn using systematic random sampling. The findings demonstrated that agreeableness, neuroticism and materialism have significant effects on Malaysian generation Y compulsive buying behaviour, where materialism is the strongest predictor among all variables tested. The results indicated that individuals’ compulsive buying behaviour in this context of study was mainly affected by their activities to engage in the development and maintenance of self through the acquisition and use of products and services that are believed to be able to provide desirable symbolic value. This study is expected to contribute in the field of consumer behaviour and Malaysian generation Y literature as it attempts to integrate three important variables that can affect compulsive buying behaviour which is personality traits (Big-Five), materialism and stress.